Extent of Market Orientation of Commercial Banks in Punjab - Sharma, Siddharth; Verma, Rajesh (Indian Journal of Marketing, 2017)
The growing competition coupled with customer desires is making it essential for the firms to implement such a concept, which can help them to develop a competitive edge over others. In this context, market orientation has gained popularity in recent years as it refers to the state of firms directed towards the market. It gives insights to understand the internal as well as external environment of an organization and equips the organization with better strategies to compete with its competitors. This paper examined the measure of the extent of market orientation of commercial banks in Punjab. In addition, a comparison was made between private-sector banks & public-sector banks and rural & urban branches of commercial banks to find out the nature of market orientation. MARKOR multi-item scale was used to measure the extent of market orientation in selected banks. This scale consisted of three constructs namely intelligence generation, intelligence dissemination, and responsiveness. Further, to serve the purpose, primary data were collected from 12 commercial banks in Punjab in February 2015. The total bank branches taken for the study were 200, out of which 100 were private-sector banks and 100 were public-sector banks. These banks were selected on the basis of their growth, profitability, efficiency, and credit quality. The results depicted that commercial banks of Punjab were considerably market oriented. However, in terms of overall andÂ dimension wise mean scores of market orientation, the public sector banks and private sector banks were significantly different from each other.